Post-sexual assault cigarette smoking: Findings from a randomized clinical trial of a video-based intervention. (January 2020) - Walsh, Kate; Gilmore, Amanda K.; Schumacher, Julie A.; Coffey, Scott F.; Frazier, Patricia A.; Ledray, Linda; Acierno, Ron; Ruggiero, Kenneth J.; Kilpatrick, Dean G.; Resnick, Heidi S.
Abstract: Sexual assault (SA) is associated with elevated risk for cigarette smoking. The current study tested whether a brief video intervention delivered in the emergency department was effective at reducing smoking following SA. Participants were 233 girls and women (age 15+) who received a SA medical forensic examination (SAMFE) and were randomized to one of three conditions: 1) Prevention of Post-Rape Stress (PPRS), a brief video designed to reduce post-SA psychopathology; 2) Pleasant Imagery and Relaxation Information (PIRI), an active control video involving relaxation training; and 3) treatment as usual (TAU). Among those who participated at baseline, 154 participants completed at least one follow-up at 1.5, 3, and 6 months after the SAMFE. Participants reported the number of days of smoking and the average number of cigarettes smoked per day in the two weeks prior to the sexual assault as well as in the two weeks prior to each follow-up. Two-thirds (68.8%) of participants smoked prior to the SA or during any follow-up. One-fifth of participants who did not smoke prior to the SA smoked at one or more follow-ups. Smoking declined on average over follow-up although TAU was associated with increased initial smoking compared to PPRS; PPRS and PIRI did not differ. SA contributes to increases in smoking and the PPRS, a brief and cost-effective video-based intervention delivered during the SAMFE, can protect against increases in post-SA smoking. Trial registration: NCT01430624 Highlights: RCT tested a brief video intervention among rape victims in the emergency room. 67% of rape victims reported smoking prior to or after the rape. Of women who did not smoke in the year before the rape, 19% smoked following the rape. The video mitigated smoking relative to treatment as usual.